The importance of simulation education for the management of traumatic cardiac injuries: a case series - Takashi Nagata; Tomohiko Akahoshi; Michiko Sugino; Wataru Ishii; Ryoji Iizuka; Takafumi Shinjo; Yoshimitsu Izawa; Michiaki Hata; Alan Kawarai Lefor (Surgical Case Reports)
Abstract Background The management of cardiac trauma requires rapid intervention in the emergency room, facilitated by a surgeon with prior experience to have good outcomes. Many surgeons have little experience in the requisite procedures. We report here 4 patients who suffered cardiac trauma, and all 4 patients survived with good neurologic outcomes. Case presentations Patient 1 suffered blunt cardiac trauma from a motor vehicle accident and presented in shock. Cardiac tamponade was diagnosed and a cardiac rupture repaired with staples through a median sternotomy after rapid transport to the operating room. Patient 2 suffered blunt cardiac trauma and presented in shock with cardiac tamponade. Operating room median sternotomy allowed extraction of pericardial clot with recovery of physiologic stability. Patient 3 presented with self-inflicted stab wounds to the chest and was unstable. She was brought to the operating room and thoracotomy allowed identification of a left ventricle wound which was repaired with a suture. Patient 4 presented in cardiac arrest with multiple self-inflicted stab wounds to the chest. Emergency room thoracotomy allowed repair of a right ventricle laceration with recovery of vital signs. Conclusions The management of all 4 patients was according to the principles taught in the ATOM course. Three of the 4 surgeons had no prior experience with management of cardiac trauma and credited the good outcomes to taking the ATOM course. These are uncommon injuries and formal training in their management is beneficial to patients.